Gesture control as assistive technology - Savita, K.S. (American Scientific Publishers, 2017)
Gesture Control as Assistive Technology offers a great use of current trend’s technology—designed to detect the human’s natural movements. By exploring the use of gestures for children in the classrooms environment, this paper deduced that the more natural and technologically oriented a specified task is, the longer the interest of a child can be kept. This system was put to good use in the classrooms of those who were diagnosed with Learning Difficulties. In current market, there are an abundance of Assistive Technologies that utilizes a touch screen, which limits the input to a 2D plane. Thus, this experiment is done by implementing natural gestures as input for the system and comparing it to mainstream touchscreens used as Assistive Technology in withholding the attention spans of children. © 2017 American Scientific Publishers. All rights reserved.